Assessing the informativeness of the controlled parameters in the task of identyfing the state of the system - Raskin, Lev Hryhorovych; Sukhomlyn, Larysa Vadymivna; Sokolov, Dmytro Dmytrovych; Domochka, Lidiia Vladyslavivna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The effectiveness of solving the problem of identifying the system state significantly depends on the number of controlled parameters and the degree of their informativeness. The traditional method for assessing the informativeness of these parameters is based on the measure of distance between the probability distributions of the values of the controlled parameter for different states of the system proposed by Kullback. The shortcomings of Kullback measure have been revealed. Firstly, the value of this measure is not normalised and is not limited from above. Secondly, this measure is asymmetric, i.e. its numerical value depends on the way its components enter the calculation ratio. The method for calculating the informativeness criterion proposed in this paper takes into account the uncertainty that arises due to the fuzzy description of the boundaries of the areas of possible values of the controlled parameters for each of the possible states of the system. An important enhancement of the known methods for assessing the informativeness of the controlled parameters is to take into account the real existing inaccuracy in estimating the values of the results of measuring these parameters themselves. These circumstances determine the subject and purpose of the study that is the development of a method for calculating the distance between the distributions of fuzzy values of the controlled parameter, free from the shortcomings of the Kullback measure. To calculate the measure of the distance between the distributions of the values of the controlled parameter under conditions of uncertainty of the initial data, described in terms of fuzzy mathematics, a symmetric criterion is proposed, which is easily calculated. Examples of the criterion calculation are given. The possibilities of increasing the level of informativeness of the criterion using analytical descriptions of membership functions of fuzzy values of the controlled parameter for different states of the system are considered.

Ефективність розв'язання задачі ідентифікації стану системи суттєво залежить від кількості контрольованих параметрів і ступеня їхньої інформативності. Традиційна технологія оцінювання інформативності цих параметрів спирається на запропоновану Кульбаком міру відстані між ймовірнісними розподілами значень контрольованого параметра для різних станів системи. Виявлені недоліки міри Кульбака. По-перше, значення цієї міри не нормоване і не обмежене зверху. По-друге, ця міра асиметрична, тобто її чисельне значення залежить від способу входження її компонентів у розрахункове співвідношення. Запропонована в роботі технологія розрахунку критерію інформативності враховує невизначеність, що виникає внаслідок нечіткості опису меж областей можливих значень контрольованих параметрів для кожного з можливих станів системи. Важливе посилення відомих технологій оцінювання інформативності контрольованих параметрів полягає у врахуванні реально існуючої неточності оцінювання значень самих результатів вимірювання цих параметрів. Зазначені обставини визначають предмет і мету дослідження – розроблення метода розрахунку відстані між розподілами нечітких значень контрольованого параметра, вільного від недоліків міри Кульбака. Для розрахунку міри відстані між розподілами значень контрольованого параметра в умовах невизначеності вихідних даних, описаних у термінах нечіткої математики, запропоновано симетричний критерій, який легко обчислюється. Наведено приклади розрахунку критерію. Розглянуто можливості збільшення рівня інформативності критерію з використанням аналітичних описів функцій належності нечітких значень контрольованого параметра для різних станів системи.
Оцінка інформативності контрольованих параметрів у завданні ідентифікації стану системи
Keywords: identification of system states; Kullback information measure; assessment of informativeness of fuzzy controlled parameter; ідентифікація станів системи; інформаційна міра Кульбака; оцінка інформативності; нечіткий контрольований параметр